Simple Financial Management Education with Lamikro for Cake and Pastry Business - Rousilita Suhendah; Christin Angelia; Clara Felixa Tridian (Journal of Innovation and Community Engagement, 2025)
Education on simple financial management using the Lamikro application carried out by the community service team with Marife Cake & Pastry as a partner aims to provide an understanding of the need to separate business and personal financial management. This training also provided education on the technical use of the Lamikro application in preparing profit and loss reports and balance sheets since this application is easy to understand for everyone. Marife Cake and Pastry, located in the Bekasi area, has difficulty managing finances. The partners of this community service program still mixed business and personal finances and had not been calculating the profit or income from the business they have been pursuing so far. The owners of this micro, small, and medium business did not yet have a good understanding of financial management and financial reporting. Marife Cake and Pastry managed its finances traditionally, not separating business finances from personal finances. As a result, this business had difficulty determining the actual business profit. To overcome this, the community service team provided training on simple financial management using the Lamikro application. This educational activity was in the form of training on managing MSME business finance and using the Lamikro application to record every financial transaction. After following the training, Marife Cake and Pastry can utilize the Lamikro application to create financial reports and manage business and personal finances separately. The owner also gains insight into the assets owned by his business.